Determination of Conducted EMI in SiC Based Dual Active Bridge Converter - Samet YALCIN; Tuna GÖKSU; Selami KESLER; Okan BINGÖL (International Journal of Applied Methods in Electronics and Computers, 2020)
Power converters are required to work faster and with higher power density with the developing technology. Therefore, the converter is expected to work in more than one direction. Usage of Dual Active Bridge DC-DC Converter is an example. To increase the power density of the converters, it is necessary to increase the switching frequency. In conventional Si MOSFET based converters, power losses are very high and cause high electromagnetic interferences at high frequencies. These disadvantages lead developers to the use of wide-band gap semiconductor based converters such as SiC However, SiC MOSFETs will also emit electromagnetic interference (EMI) above a certain frequency. In this study, the EMI, emitted at certain frequencies by the Dual Active Bridge (DAB) DC-DC Converter, is simulated by the LTspice. It was observed that the Si-based inverter parts of the DAB converter generate 10 V EMI on the linear base, that means 140 dBµV EMI on the logarithmic base, at 20 kHz. The SiC-based converter does not emit any noise at the same frequency. However, when the frequency was increased to 250 kHz, it was determined that the SiC based converter emitted 2.3 V noise on the linear base, thus 123 dBµV noise on the logarithmic base. This study shows that not only Si MOSFET’s but only SiC MOSFET’s emit EMI over a certain frequency.